Internal phosphorus loading contributions from deposited and resuspended sediment to the Lake of the Woods. (2nd October 2017) - James, William F.
ABSTRACT: James WF. 2017. Internal phosphorus loading contributions from deposited and resuspended sediment to the Lake of the Woods. Lake Reserv Manage. 33:347–359. The Lake of the Woods exhibits cyanobacterial blooms despite substantial declines in watershed phosphorus (P) loading since the 1970s, suggesting that internal P loads are contributing to the P budget. A better understanding of internal P loading contributions and dynamics is needed to refine management strategies and water quality goals. Sediment cores were collected from several stations within the US portion to examine potential internal P contributions from deposited and resuspended sediment. Although laboratory-derived diffusive P fluxes were highest under anaerobic conditions (8−12 mg/m 2 d), aerobic conditions at the sediment–water interface may regulate in situ diffusive P fluxes due to frequent polymixis. Although much lower under aerobic conditions, modest fluxes of 0.2−0.6 mg/m 2 d could play an important role in the P budget. Simulated resuspension indicated that the critical shear stress of deposited sediment was relatively low at 1.3−2.3 dynes/cm 2 . The wind-exposed long fetches and shallow morphometry of regions of Lake of the Woods could result in frequent resuspension of P-enriched clays and silts that contribute inorganic P to the water column. Resuspended sediments exhibited a low equilibrium P concentration (near zero) and high linear adsorption coefficient (700−3200 L/kg), suggesting they may act more as a sink rather than a source for soluble P. Resuspension could compete with cyanobacterial uptake by sequestering soluble reactive P. Resuspended inorganic P could also constitute a significant portion of the water column total P composition in addition to organic P, incorporated as cyanobacterial biomass, and needs to be considered in the P budget and chlorophyll prediction.